The novel ER stress inducer Sec C triggers apoptosis by sulfating ER cysteine residues and degrading YAP via ER stress in pancreatic cancer cells - Junxia Wang; Minghua Chen; Mengyan Wang; Wenxia Zhao; Conghui Zhang; Xiujun Liu; Meilian Cai; Yuhan Qiu; Tianshu Zhang; Huimin Zhou; Wuli Zhao; Shuyi Si; et al. (Elsevier, 2022)
Pancreatic adenocarcinoma (PAAD) is one of the most lethal malignancies. Although gemcitabine (GEM) is a standard treatment for PAAD, resistance limits its application and therapy. Secoemestrin C (Sec C) is a natural compound from the endophytic fungus Emericella, and its anticancer activity has not been investigated since it was isolated. Our research is the first to indicate that Sec C is a broad-spectrum anticancer agent and could exhibit potently similar anticancer activity both in GEM-resistant and GEM-sensitive PAAD cells. Interestingly, Sec C exerted a rapid growth-inhibiting effect (80% death at 6 h), which might be beneficial for patients who need rapid tumor shrinkage before surgery. Liquid chromatography/mass spectrometry and N-acetyl-l-cysteine (NAC) reverse assays show that Sec C sulfates cysteines to disrupt disulfide-bonds formation in endoplasmic reticulum (ER) proteins to cause protein misfolding, leading to ER stress and disorder of lipid biosynthesis. Microarray data and subsequent assays show that ER stress-mediated ER-associated degradation (ERAD) ubiquitinates and downregulates YAP to enhance ER stress via destruction complex (YAP-Axin-GSK-βTrCP), which also elucidates a unique degrading style for YAP. Potent anticancer activity in GEM-resistant cells and low toxicity make Sec C a promising anti-PAAD candidate.